2016
DOI: 10.3389/fneur.2016.00059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Blast Overpressure on Retina and Optic Tract in Rats

Abstract: Blast has been the leading cause of injury, particularly traumatic brain injury and visual system injury, in combat operations in Iraq and Afghanistan. We determined the effect of shock tube-generated primary blast on retinal electrophysiology and on retinal and brain optic tract histopathology in a rat model. The amplitude of a- and b-waves on the electroretinogram (ERG) for both right and left eyes were measured prior to a battlefield simulation Friedlander-type blast wave and on 1, 7, and 14 days thereafter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…Sham‐exposed rats were subjected to the same procedures but were placed outside the overpressure shockwave. Compared to other models using shockwave exposure inside the shock tube, the peak overpressure magnitudes from this model are slightly greater (Sajja et al ., ; DeMar et al ., ; Perez‐Garcia et al ., ; Wang et al ., ; Toklu et al ., ). However, peak shockwave overpressure is not the most appropriate injury metric.…”
Section: Methodsmentioning
confidence: 99%
“…Sham‐exposed rats were subjected to the same procedures but were placed outside the overpressure shockwave. Compared to other models using shockwave exposure inside the shock tube, the peak overpressure magnitudes from this model are slightly greater (Sajja et al ., ; DeMar et al ., ; Perez‐Garcia et al ., ; Wang et al ., ; Toklu et al ., ). However, peak shockwave overpressure is not the most appropriate injury metric.…”
Section: Methodsmentioning
confidence: 99%
“…A key requirement of blast models is the documentation of peak overpressures and their duration to ensure that the experimental design produces blast exposures comparable to what soldiers and civilians experience on the battlefield (Courtney & Courtney, ; Goldstein, McKee, & Stanton, ). Free‐field explosions (Hines‐Beard et al, ; Kuehn et al, ), shock tubes (DeMar et al, ; Petras et al, ), blast tubes (Elder, Stone, & Ahlers, ), and custom fabricated devices such as a modified nail gun (Kuehn et al, ) and a modified paint ball gun (Bricker‐Anthony, Hines‐Beard, & Rex, ; Bricker‐Anthony & Rex, ; Hines‐Beard et al, ; Guley et al, ; Heldt et al, ; Reiner et al, ) have been used to simulate primary blast injury. Advantages of the aforementioned custom fabricated models are low cost assembly, ease of use and the ability to isolate specific parameters of interest due to control of blast directed injury to the whole head (brain and eyes), specific regions of the cranium (brain only), and orbit (eye only).…”
Section: Visual System Pathology From Blast Injury In Animalsmentioning
confidence: 99%
“…Similar to humans, visual deficits from blasts in animals (Table ) can occur soon after blast and remain progressive. Several studies (Bricker‐Anthony et al, ; Bricker‐Anthony & Rex, ; DeMar et al, ; Mohan et al, ) highlight the importance of blast wave directionality in rodents. One study (Guley et al, ) in mice evaluating visual system deficits found that a single blast directed unilaterally onto a small portion of the cranium produced noticeable axonal damage.…”
Section: Visual System Pathology From Blast Injury In Animalsmentioning
confidence: 99%
See 2 more Smart Citations